Neural Network Backstepping Controller Design for Uncertain Permanent Magnet Synchronous Motor Drive Chaotic Systems via Command Filter - Luo, Ricai; Deng, Yanping; Xie, Yuling (Frontiers in Physics, 2020)
In this study, an adaptive neural network (NN) command filtered control (CFC) method is proposed for permanent magnet synchronous motor (PMSM) system with system uncertainties and external disturbance by means of backstepping technique. At every backstepping step, a novel command filter is proposed, and the complicated virtual input and its derivative together can be approximated by this filter. The ``explosion of complexity" problem in conventional backstepping design can be avoided because we do not need to calculate the derivative of the virtual input repeatedly. NNs are used to model system uncertainties and disturbances. Finally, an adaptive NN CFC is designed, and the convergence of the tracking error and the boundedness of all signals involved can be guaranteed. Finally, a simulation study is presented to verify the theoretical results.